2019
DOI: 10.1101/654756
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemical Impacts of the Microbiome Across Scales Reveal Novel Conjugated Bile Acids

Abstract: samples 33 PCD, RK, SM, VN and DS guided experimental design and analysis. 34 MW converted the data in GNPS, developed spectral search and molecular explorer. 35 TT, VN and SM raised animals and guided experimental design. 36 RQ and PD wrote the manuscript 37 38Abstract 39 A mosaic of cross-phyla chemical interactions occurs between all metazoans and their 40 microbiomes. In humans, the gut harbors the heaviest microbial load, but many organs, 41 particularly those with a mucosal surface, associate with highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Indeed, we showed that Clostridium spp. were found to produce this bile acid [36]. This result demonstrates mmvec's ability to streamline the discovery of microbes that produce specific molecules of interest in vivo.…”
Section: Effects Of High Fat Diet In Murine Model Case Studymentioning
confidence: 72%
See 1 more Smart Citation
“…Indeed, we showed that Clostridium spp. were found to produce this bile acid [36]. This result demonstrates mmvec's ability to streamline the discovery of microbes that produce specific molecules of interest in vivo.…”
Section: Effects Of High Fat Diet In Murine Model Case Studymentioning
confidence: 72%
“…We then tested whether mmvec could determine the microbial origin of specific molecules in a complex biological system. We recently discovered a new kind of bile acid, where cholate is conjugated to amino acids other than glycine and taurine [36]. These molecules increased in abundance with high-fat diet in humans.…”
Section: Effects Of High Fat Diet In Murine Model Case Studymentioning
confidence: 99%
“…The 3D mouse model was generated as described previously (Quinn et al 2019). In brief, MRI images were acquired at the UCSD Center for Functional MRI from a euthanized 8-wk-old female C57BL/6 mouse with a Bruker 7T/20 MRI scanner using a quadrature birdcage transceiver.…”
Section: D Mouse Modelmentioning
confidence: 99%
“…Understanding how the gut microbiota influence the brain, and the complex network of molecules and neurotransmitters that mediate this influence, is a significant challenge requiring novel tools and approaches. Mass spectrometry imaging (MSI) is a molecular imaging tool that can be applied to understand and map biological systems with recent successes in mapping microbial interactions with their environment ( 3638 ). MSI maps the distribution of small molecules across a tissue section independent of any label, so no prior knowledge of the molecules present is required.…”
Section: Introductionmentioning
confidence: 99%